Factors that influence the perception of students about the importance of physical education - García Vélez, Antonio Joaquín; Jiménez Parra, José Francisco (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Currently, an increase in sedentary behaviors has been observed in young people due to changes in the motivations and interests of the students. For this reason, it was proposed to know the factors that influence the perception of students about the importance of Physical Education (PE). For this, there were 780 Primary and Secondary students from the Region of Murcia, who were administered the Attitudes towards PE Questionnaire (CAEF). Regarding the results, it was observed that the variables that mainly influence the perception of the importance of PE are the good relationship with the teacher of the area, the increase in mood after the classes and the belief that the contents are valuable. Therefore, it is concluded that PE must have a curriculum with valuable and useful content, establish a good classroom climate and use a methodology that encourages the perception of competence and belonging to the group.